2013
DOI: 10.1152/ajprenal.00717.2012
|View full text |Cite
|
Sign up to set email alerts
|

HIV compromises integrity of the podocyte actin cytoskeleton through downregulation of the vitamin D receptor

Abstract: compromises integrity of the podocyte actin cytoskeleton through downregulation of the vitamin D receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…These studies indicate that APOL1Vs may cause particularly severe renal injury in the setting of HIV infection. In a previous study, we noted that HIV increased lysosomal enzyme cathepsin L activity, which further compromised the integrity of the podocyte cytoskeleton (7). Taken together, we speculate that APOL1Vs and HIV may act synergistically on such lysosomal damage, leading to enhanced leakage of lysosomal components, exceeding the capacity to deal with damaged lysosomes by normally available pathways, and stronger cytosol cathepsin L activity than in the case of either APOL1Vs or HIV alone.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These studies indicate that APOL1Vs may cause particularly severe renal injury in the setting of HIV infection. In a previous study, we noted that HIV increased lysosomal enzyme cathepsin L activity, which further compromised the integrity of the podocyte cytoskeleton (7). Taken together, we speculate that APOL1Vs and HIV may act synergistically on such lysosomal damage, leading to enhanced leakage of lysosomal components, exceeding the capacity to deal with damaged lysosomes by normally available pathways, and stronger cytosol cathepsin L activity than in the case of either APOL1Vs or HIV alone.…”
Section: Discussionmentioning
confidence: 58%
“…Lysosomes were stained with Lucifer yellow (Invitrogen) and LysoTracker Red (Invitrogen) as described previously (6,7). Briefly, cells were cultured overnight in the medium containing 1 mg/ml Lucifer yellow, and then 500 nM LysoTracker was added followed by an additional 30-min incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, HIV-induced down regulation of VDR expression was associated with ROS generation, lysosomal cathepsin-L leak and loss of integrity of podocyte actin cytoskeleton (16); whereas, restoration of VDR expression provided protection. These studies indicated that VDR expression is critical for the maintenance of kidney cell phenotype in HIV milieu.…”
mentioning
confidence: 99%
“…This phenomenon may also be due to direct viral injury to the kidney, accelerated organ aging or individual dietary habits (19) . Direct viral infection of renal epithelial cells disturbs podocyte structure and function with subsequent upregulation of renin-angiotensin system which is held to central to the pathophysiology of hyperfiltration (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%